Therapeutic Effects of Sodium Hyaluronate and Diclofenac Sodium in Chronic Arthritis - Bogzil, Alsadek H; Shams, Gamal; El-Latif, Sohair Abd (Asian Journal of Pharmaceutical Research and Development, 2019)
The present study was designed to compare the anti-inflammatory effect of sodium hyaluronate, which is similar to the lubricant fluid that found naturally in the capsule of the healthy joint with diclofenac sodium, a member of NSAIDs commonly used in treatment of Osteoarthritis (OA), separately and in combination on an experimental model of osteoarthritis in rats induced by monosodium-iodoacetate (MIA). Twenty-five male albino rats weighing at the beginning of the experiment 160± 20 gm were used in this study. Rats were housed in cages at 25± 0.5°C. The rats were divided into 5 main groups.